The inflammatory response as a target to reduce myocardial ischaemia and reperfusion injury - Steffens, Sabine; Montecucco, Fabrizio; Mach, François (Thrombosis and Haemostasis, 2009)
Acute myocardial infarction is the leading cause of morbidity and mortality in the adult population of developed and developing nations. Although the prompt restoration of antegrade blood flow in the infarct-related coronary artery is the mean therapy for improving survival, reperfusion itself may cause damage to ischaemic myocardial tissue. This event is well known as “reperfusion injury”. Crucial mediators for cardiac damage in the reperfusion phases are oxidative stress, inflammation and leukocyte infiltration. Already approved and novel therapies might directly reduce these inflammatory processes. Treatments modulating chemokine secretion and activity should be considered as very promising approaches to reduce myocardial reperfusion injury.
Keywords: Acute myocardial infarction; chemokines; inflammation